Penyalahgunaan Mobil Dinas di Tinjau dari Undang-Undang Nomor 31 Tahun 1999 Juncto Undang-Undang Nomor 20 Tahun 2001 Tentang Pemeberantasan Tindak Pidana Korupsi di Lingkungan Pemerintahan Kota Kupang - Krisanti Maria Nana; Daud Dima Tallo; Bhisa Vitus Wihelmus (Jurnal Hukum dan Sosial Politik, 2024)
The purpose of this research is to analyze the misuse of official cars in review of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the eradication of criminal acts of corruption in the Kupang City Government. This research uses Empirical Legal Research method with primary data legal sources collected through interviews with respondents and observation of the research location as well as secondary legal data sources collected through literature study or document study. The results of the research indicate that the misuse of official cars related to the crime of corruption, namely abuse of authority in this case the misuse of official cars in the crime of corruption refers to the formulation of Article 3 of the Law on Criminal Acts of Corruption (UUTPK), namely with the aim of benefiting oneself or another person or a corporation abusing the authority, opportunity or means available to him because of his position or position that can harm state finances. Law enforcement against the misuse of official cars outside the office, namely: preventive law enforcement and repressive law enforcement. From the results of the study, the researcher concluded that the regulation of the minister of home affairs number 7 of 2006 concerning the standardization of local government work facilities and infrastructure article 1 letter g, what is meant by official vehicles is government property that is used only for official purposes, consisting of individual service vehicles, operational service vehicles / official service vehicles, and special service vehicles / fields.Conclusion related to law enforcement efforts against the misuse of official cars outside the office, namely carried out by preventive and repressive actions.